Network-Pharmacology-Guided Validation of Phyllanthus niruri Nephroprotection Against Doxorubicin: An In Vitro–In Vivo Translational Study - Rachmat Hidayat; Vania Delma; Indri Yani Septiana (Eureka Herba Indonesia, 2025)
Doxorubicin is a corner-stone anthracycline chemotherapeutic whose clinical utility is constrained by dose-limiting nephrotoxicity, and no approved pharmacological prevention currently exists. Phyllanthus niruri L. (Family Phyllanthaceae) — locally known in Indonesia as meniran — is a phytotherapeutic herb whose constituents (phyllanthin, hypophyllanthin, quercetin, rutin, gallic acid, and corilagin) target oxidative-stress and inflammatory pathways implicated in doxorubicin renal injury. We applied a tiered translational design: (i) network-pharmacology discovery using SwissTargetPrediction, TCMSP, GeneCards, and OMIM intersected six P. niruri active compounds with 842 nephrotoxicity-associated genes, identifying six hub targets (TNF, IL6, NFKB1, CASP3, BAX, BCL2) and four enriched KEGG pathways (TNF signaling, MAPK, PI3K-Akt, Apoptosis); (ii) in vitro validation in HK-2 human proximal tubular cells exposed to doxorubicin (2 µM, 24 h) with or without standardised P. niruri 70% ethanolic extract (25, 50, 100 µg/mL); and (iii) in vivo validation in 48 male Sprague-Dawley rats (eight per arm) given a single intraperitoneal dose of doxorubicin (15 mg/kg) and oral P. niruri at 100, 200, or 400 mg/kg/day for 14 days. P. niruri produced a dose-dependent rescue of HK-2 viability (84.6% at 100 µg/mL versus 41.8% in doxorubicin-only controls; p < 0.001) and reduced serum creatinine, blood urea nitrogen, urinary KIM-1, and NGAL by 55–70% at the 400 mg/kg dose with concordant restoration of glutathione and superoxide dismutase. Network-pharmacology hub targets showed transcriptionally coherent modulation. The findings support standardised P. niruri ethanolic extract as a mechanism-anchored herbal candidate for adjunctive prevention of doxorubicin-induced kidney injury, warranting clinical translation.